Determination of color changes during the drying time of ink in offset printing - ÖZOMAY, ZAFER (My University, 2010)
In the sheet-fed offset printing technique, the ink physically and chemically drying in accordance with the surface structure of the printing material. Dried ink needs to give a good colour intensity, while constituting a thin film on the surface of printing materials. In this study, the printed ink\"s L *(lightness), a*(red-green), b*(yellow-blue) assets in definite times were measured which change depending on drying in offset printing. With these measures done in the 0, 15, 30, 45, 60 and 90. minutes on spectrophotometer standart drying conditions, how to be affected the color spaces by the drying and the settlement process\" effect on color spaces was examined. The obtained valves were formed in tables and the drying behaviours and the Delta E varietions were carried out. With color valves obtained from CIE L*a*b* kind, in which levels high color exchange occured were determined.
Keywords: Harita Mühendisliği-Geomatik; Mühendislik ve Teknoloji; Geotechnical Engineering; Engineering and Technology; MÜHENDİSLİK, ÇOK DİSİPLİNLİ; Mühendislik; Mühendislik, Bilişim ve Teknoloji (ENG); ENGINEERING, MULTIDISCIPLINARY; ENGINEERING; Engineering, Computing & Technology (ENG); Genel Mühendislik; Medya Teknolojisi; Mühendislik (çeşitli); Fizik Bilimleri; General Engineering; Media Technology; Engineering (miscellaneous); Physical Sciences; color changes; CIE L*a*b*